THE CONCEPT «WORLD» IN THE CONCEPTOSPHERE OF THE ANDREY BELYI’S NOVEL «PETERSBURG» - Кулєшова, Людмила (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
The article is devoted to the problem of the functioning of the concepts in the texts of fiction. A conceptual analysis of the work of the Russian writer Andrey Bielyi «Petersburg» is made. Such an analysis involves the selection of key concepts of the conceptual sphere of the novel, reflecting the artist's artistic conception and the structure of his artistic reality. For the novel Petersburg, one of these key concepts is the concept «world». The purpose of the article is to reveal the semantic content and place of the concept «world» in the conceptual sphere of Andrei Belyi's «Petersburg» novel. Results. In the paradigmatic aspect, the concept of «world» is related to the concepts of «universe», «space», «existing». With this relationship, the basic meanings of the «world» concept are highlighted: the universe filled with things and meaning, an ordered reality, a kind of living whole, totality that goes beyond the limits of earth reality. In the syntagmatic aspect, the concept «world» correlates with groups of lexemes denoting the state of the world, its spatial properties, divisions and isolation, objects and phenomena related to man. This attitude highlights the basic meanings of the «world» concept: multiplicity and diversity, the world as the repository of everything, the human world (more specifically, the world of the characters of the novel «Petersburg»). The concept of «world» also reflects intertextual relations, associated with different spheres of culture: philosophical and esoteric, sociohistorical, the sphere of knowledge in the field of human psychology. On this side, the world in the novel «Petersburg» appears as the duality of the visible and invisible, physical and astral, earthly and otherworldly; as humanity as a whole, as all parts of the world and the sequence of epochs; as the inner world of man. The article formulates the principles of conceptual analysis, which include the allocation of paradigmatic relations of the concept, syntagmatic relations and intertextual (general cultural) relations. The application of these principles to the concept of «world», implemented in the text of the novel «Petersburg» led to the establishment of a number of semantic features of the analyzed concept.All the meanings highlighted by the analysis are interconnected in the text of the novel «Petersburg», the means of their connection are subject lines, composition, relationships and actions of the characters. It can be said that the concept of «world» is broken down in the novel «Petersburg» into a mutually complementary and passing from one state into another set of images, aspects, pictures of the world.